2003
DOI: 10.1128/jcm.41.1.227-236.2003
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assessment Program for Genotypic Antiretroviral Testing Improves Detection of Drug Resistance Mutations

Abstract: Genotypic antiretroviral testing is now widely used for the management of patients who are undergoing antiretroviral therapy for human immunodeficiency virus infection. The assays are complex, and there is considerable potential for variation between laboratories. Informative and ongoing quality assessment programs (QAPs) which address all aspects of testing are required. The panel distribution of clinical material is a critical component of QAPs. We report on the results and data from a recent panel. Four cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 17 publications
2
28
0
1
Order By: Relevance
“…This would mean that if a mixed base is represented in the GCS, then data returned by a laboratory should show a mixed base in the same position to be considered homologous. Sequence homology to a group consensus sequence was shown to be slightly lower by Sayer et al (8), but these results may be influenced by the high proportion of in-house assays in the group evaluated (six of nine laboratories). Although some samples in our study displayed Ͻ98% concordance to the GCS, it is possible that the discrepancies were generated in part by the use of RUO kits where less-stringent quality control of kit reagents was in place.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…This would mean that if a mixed base is represented in the GCS, then data returned by a laboratory should show a mixed base in the same position to be considered homologous. Sequence homology to a group consensus sequence was shown to be slightly lower by Sayer et al (8), but these results may be influenced by the high proportion of in-house assays in the group evaluated (six of nine laboratories). Although some samples in our study displayed Ͻ98% concordance to the GCS, it is possible that the discrepancies were generated in part by the use of RUO kits where less-stringent quality control of kit reagents was in place.…”
Section: Discussionmentioning
confidence: 91%
“…The ability to accurately report the identity of each nucleotide at each position along the template could be considered in the assessment and evaluation of genotyping proficiency. This issue was also described by Sayer et al (8) in their analysis of, predominantly, in-house assays and by Shafer et al, who examined replicate testing by two laboratories also using inhouse assays (9). In our testing, all laboratories used the same sequencing platform and the group consensus sequence for each sample was generated by alignment using a 60% threshold.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV genotyping is routinely performed by Sanger sequencing of plasma HIV RNA; however, this technology is too costly and technically demanding to implement in most low-resource laboratories and clinics. Furthermore, the sensitivity of consensus sequencing is limited for minor variants constituting Ͻ25% of the viral population (7,8), although low-frequency HIV drug resistance mutations, particularly involving resistance to nonnucleoside reverse transcriptase (RT) inhibitors (NNRTIs), have been associated with increased risks of virological failure with first-line ART (9)(10)(11)(12)(13)(14)(15). Therefore, sensitive and affordable assays are needed to monitor HIV drug resistance as part of global HIV treatment programs.…”
mentioning
confidence: 99%
“…Shafer et al (69) previously showed that most discordances between two laboratories were due to inherent sampling variation in sequencing a heterogeneous population rather than exogenous differences in the sequencing process. However, Sayer et al (66) found that nine laboratories processing the same set of HIV-1 protease and RT samples varied consistently in their rates of reporting mixtures. They were unable to resolve whether differences in reporting mixtures were due to experimental procedures or subsequent sequence editing.…”
Section: Discussionmentioning
confidence: 99%